Flood Modeling of Telomoyo Watershed in Kebumen Using HEC-RAS for Mapping Flood Risk Zones - Khalid S Ridwan; Sely Novita Sari; Anggi Hermawan (G-Tech: Jurnal Teknologi Terapan, 2025)
Flooding is a frequent natural disaster in Indonesia, especially in areas with low topography and high rainfall. The Telomoyo watershed in Kebumen Regency, with an area of 553.22 km², faces a high risk of flooding even though its water flow is controlled by the Sempor Reservoir. Geographical conditions, topography and high rainfall in the upstream area often cause inundation in the downstream area. This study modeled the flood potential in the Telomoyo watershed using HEC-RAS software, based on rainfall data and a Digital Elevation Model (DEM). The methodology includes hydrological analysis to determine peak discharge using the Nakayasu Synthetic Unit Hydrograph (HSS) method and hydraulic analysis to map flood-prone areas. The results showed that the combination of rainfall and topographic data resulted in accurate mapping of flood-prone areas. The peak discharge of the 25-year return period reached 986.177 m³/second, with inundation up to a depth of more than 3 meters in certain areas. Integration of satellite rainfall data from NASA's Giovanni with 2D hydraulics modelling based on HEC-RAS, which produced flood risk maps for the Telomoyo watershed with a high level of accuracy that was previously under-explored. The outcome of this research for flood management in the Telomoyo watershed is the provision of a scientific basis for more effective mitigation strategies, such as strengthening drainage infrastructure, and risk zone-based spatial planning. This information can be used as a basis for more effective flood mitigation planning and risk management in the Telomoyo watershed area.